Enantioselective Bromolactonization of Deactivated Olefinic Acids: Studies Toward the Synthesis of Brominated Isochroman-1,4-diones - Li, Danqing; He, Hailong; Huang, Xiaodan; Yu, Pei; Jiang, Xiaojian (SynOpen, 2018)
Enantioselective bromolactonization using an amino-carbamate catalyst to generate brominated isochroman-1,4-diones is described. Excellent yields and moderate enantioselectivities were achieved.
Keywords: isochroman-1,4-diones; bromolactonization; organocatalysis; enantioselectivity; deactivated olefins